A Multi-Site Proof-of-Concept Investigation of Computerized Approach Avoidance Training in Adolescent Cannabis Users - Jacobus, Joanna (Drug Alcohol Depend, 2018)
BACKGROUND: Few effective treatment options exist for cannabis-using youth. This pilot study aimed to test Approach Avoidance Training to reduce cannabis use with non-treatment seeking adolescents. METHODS: Eighty cannabis-using non-treatment-seeking adolescents (average age 19) were recruited from San Diego, California and Charleston, South Carolina, and randomized to complete either six sessions of Cannabis Approach Avoidance Task Training (CAAT-training) designed to reduce automatic approach biases for cannabis cues, or CAAT-sham training. Change in two primary outcome variables were examined: 1) cannabis approach bias and 2) percent cannabis use days over study enrollment. Change in percent alcohol use days over study enrollment was explored as a secondary outcome. RESULTS: A mixed models repeated measures analysis confirmed the group by time interaction effect for approach bias failed to reach statistical significance (p=.06). Significant group by time interaction effects (ps<.05) predicted percent days of cannabis and alcohol use over study enrollment. Participants randomized to the avoid cannabis condition (CAAT-training) reported 7% less days of cannabis use compared to 0% change for sham; unexpectedly, those in the avoid cannabis condition reported 10% percent more alcohol use days compared to 3% more for sham. CONCLUSIONS: Computerized cognitive bias modification paradigms may have utility in reducing adolescent cannabis use. Future work should consider developing a paradigm that addresses both cannabis and alcohol, as well as alternative computerized approaches for coping with addictive behavior in conjunction with bias modification. CLINICALTRIALS.GOV IDENTIFIER: NCT02723149